A conceptual study on landlord and tenant law in peninsular Malaysia: a focus on private residential tenancy - Sufian, Azlinor (Thompson Reuters, 2012)
Unlike other jurisdictions such as the UK, Australia, New Zealand and Canada, Malaysia does not have legislation that deals specifically with landlords and tenants. Thus, a tenancy agreement can be concluded either orally or in writing. As such the rights and obligations of both parties are depending on the terms and conditions of the contract entered by them. The problem would arise if both a landlord and tenant are not equal in footing in terms of bargaining power. Hence their rights either as a landlord or tenant may not be well protected. Obviously there is no specific law dealing with rent control and other related matters that lead to tenancy disputes. These include issues on security and rental deposit, quality and safety of the rented houses, termination, eviction and a mechanism for dispute settlement. While provisions on tenancies and leases can be found in the National Land Code 1965, Contracts Act 1950, Distress Act 1951 and Specific Relief Act 1950, the existing legislation remains rather vague and deals with the issue in piecemeal. The question thus arises whether a comprehensive law in a single statute is really needed to regulate landlords and tenants in Peninsular Malaysia? Adopting the qualitative research methodology, this conceptual paper will focus on the relationship between landlord and tenant in private residential tenancy. It is the aims of this paper to identify key legal issues in landlord and tenant relationship in this sector and to examine the adequacy of existing legal framework. The reported cases on landlord and tenant may become evidences as to the need of a specific landlord and tenant law in Peninsular Malaysia, in particular for private residential tenancy. The best practices from Scotland are taken as reference, whenever necessary. The findings of the research found that based on laws and practices in these two jurisdictions, it is very significant to have specific law to regulate the relationship between landlord and tenant in private residential tenancy in order to protect the interest of all parties involved.